Infestation of ectoparasites in Gudusia chapra (Hamilton) - Khanum, Hamida; Khan, Haroon Or Rashid; Farhana, Rimi (University Journal of Zoology, Rajshahi University, 2007)
One hundred Gudusia chapra ranging from 6 to 17 cm were examined on monthly basis. Of 100 fishes, 32 were male and 68 were female, sex ratio being 1:2.1. A total of 163 parasites were recovered from the host, which 70% were trematodes and 16% copepods. The overall prevalence of infection was 86% and the mean±SD intensity was 1.89±0.91. Heavy infestations (100%) were recorded in males of the largest (14.25-17.0 cm) and the smallest (6.0-8.75 cm) length groups. Total infection rate was also higher in males (87.72%) than in females (83.82%). Intensity of infestation in males and females was 1.62 and 2.03, respectively. Key words: Gudusia chapra, ectoparasites, trematode, copepod, infestation intensity Univ. j. zool. Rajshahi Univ. Vol.25 2006 p.23-25